Agricultural Extension’s Key Role in Modern Crop Cultivation: A Review (Agro-Science Letters, 2026)
Agricultural Extension (AE) serves as a cornerstone of contemporary  farming by bridging the gap between scientific knowledge generated at  research institutions and the practical needs of farmers, ultimately driving  improvements in agricultural productivity and long-term sustainability. Its  significance is amplified in the current era, where the compounding pressures  of climate variability and volatile market conditions require farmers to be  adaptive and responsive. AE functions as a conduit through which advances  in crop management, farming technologies, and scientific innovations are  made accessible to farming communities, including those in geographically  isolated and resource-limited areas. This review explores the multifaceted  contributions of AE to Indian agriculture, with particular attention to  its roles in translating research outputs for farmers, building technical  capacities, guiding efficient production strategies, and strengthening  resilience against environmental and economic risks. As India confronts  growing threats from climate change alongside persistent food security  concerns, AE assumes an even more critical function. Emerging digital tools  such as artificial intelligence platforms and immersive virtual technologies  offer transformative possibilities for delivering extension services; however,  their adoption must be guided by principles of inclusivity, particularly  in addressing unequal access to digital infrastructure and varying levels  of digital competency among farming populations. Structural barriers  including insufficient funding, socio-cultural constraints, and fragmented  policy frameworks continue to challenge the effectiveness of extension  systems. Addressing these requires sustained innovation and systemic  reforms. Going forward, AE will remain indispensable in navigating the  evolving agricultural landscape of India, with continued investment needed  to enhance its reach and responsiveness.
Keywords: Artificial intelligence; Climate change; Modern crop; Digital transformation